Diffusion tensor imaging (dti) and fibre tractography of younger and older adults - Sakaran, Sharmila Sandra (Universiti Sains Malaysia, 2016)
Diffusion Tensor Imaging (DTI) is promising method of advanced magnetic resonance imaging (MRI) technique. DTI is able to characterize microstructural changes and provide quantitative information about tissue properties. The information is in the form of parameter indices e.g. apparent diffusion coefficient (ADC), fractional anisotropy (FA) and visualization of neuron fibres through a particular technique called fibre tractography. Few previous studies have reported degradation of neural fibres and its effect on diffusion of water molecule in aging brain. The aim of this study is to compare DTI and number of fibres of CC and CST fibre bundle between young and old healthy subjects. Two main white matter fibre bundles in human being were observed which are Corpus Callosum (CC) and Corticospinal tract (CST) regions. Using retrospective method, two sets of DTI images of healthy female subjects that are a young adult aged 30 year old and old adult aged 56 year old were taken at Advanced Medical and Dental Institute University Sains Malaysia (AMDI-USM), for one to one comparison study. Region of interests were located in the CC and CST area. Comparison of ADC, FA and number of fibres was made between young subject and old subject. No significaant differences were observed in ADC and FA value between young and old subject. The percentage of difference between both subject for ADC value in CC and CST are 0.06% and 5% respectively. Whereas, the percentage difference in FA are 0.1% and 0.5% respectively. However, fibre tractography showed lesser number of fibres in old subject compared to young subject for both regions with percentage difference for CC is 6.28% and for CST 100.8%. In conclusion, no differences found in ADC and FA value between young and old subjects. However, fibre tractography revealed reduced number of fibres in old subject compared to young subject.